Cisco TCP/IP routing professional reference - Lewis, Chris (Christopher S) (Cisco technical expert., 1999)
This hands-on manual provides solutions to everyday Cisco problems. It includes coverage on internetworking Cisco Routers with IPv6, and on Cisco Routers and Firewalls.